Aβ misfolding in blood plasma measured by immuno‐infrared‐sensor as an age‐independent risk marker of Alzheimer's disease. Issue 1 (10th February 2021) - Möllers, Tobias; Stocker, Hannah; Perna, Laura; Nabers, Andreas; Rujescu, Dan; Hartmann, Annette M.; Holleczek, Bernd; Schöttker, Ben; Gerwert, Klaus; Brenner, Hermann
Abstract: Introduction: Determining potential risk factors of amyloid beta (Aβ) misfolding in blood, a risk marker for clinical Alzheimer's disease (AD), could have important implications for its utility in future research and clinical settings. Methods: Participants aged 50 to 75 years attending a general health examination were recruited for a prospective community‐based cohort study in Saarland, Germany, in 2000 to 2002. For these analyses, participants with available Aβ misfolding measurements and clinical AD information at 17‐year follow‐up were included ( n = 444). Results: Age did not show any association with Aβ misfolding in plasma; however, a strong association of both age and Aβ misfolding with the incidence of clinical AD was evident. Education and cardiovascular diseases were likewise not associated with Aβ misfolding. Discussion: Structural measurement of Aβ misfolding in blood plasma is an age‐independent risk marker of clinical AD among older adults, supporting that risk of clinical AD is already largely determined before older adulthood.